(untitled) (Balneo and PRM Research Journal, 2024)
The necessity to improve the quality of health services is a growing concern of all stakeholders involved in providing medical assistance. Effective communication establishes interpersonal relationships with patients, enabling timely and accurate treatment decisions. This study aimed to assess the perception of Medical Rehabilitation specialists regarding the usage of Marketing Communication principles. It was conducted in the The National Center of Neurorehabilitation for Children “ Dr. N. Robănescu” Bucharest, Romania and included 85 participants with the following positions: physicians, psychologists, physiotherapists and medical assistants. According to the findings, 80% of medical staff stated that all useful information is provided to patients in a clear and accurate manner, which is also the desired quality management. In the current study, “face-to-face” communication was found to be the most successful method of communication.